Applying multispecies justice in nature-based solutions and urban sustainability planning: Tensions and prospects - Christopher M. Raymond; Pauliina Rautio; Nora Fagerholm; Valtteri A. Aaltonen; Erik Andersson; Danielle Celermajer; Mike Christie; Maria Hällfors; Maria Helena Saari; Himansu Sekhar Mishra; Alex M. Lechner; Melissa Pineda-Pinto; et al. (npj Urban Sustainability)
Abstract While substantial efforts have been made to identify and address issues of environmental justice in urban areas, the question of how to consider and plan for the concerns of humans and other species remains a major challenge. This paper provides a conceptualisation of what 'justice' might mean from a multispecies justice (MSJ) perspective within the contexts of nature-based solutions (NBS) and urban sustainability planning. We offer a wider conceptualisation of representation, distribution and agency compared with dominant framings in NBS scholarship and provide exemplar cases on how to integrate these concepts in planning discourse. We critically discuss some of the challenges and opportunities of considering MSJ when confronted by established procedures and practices in NBS science and decision-making, focusing on (i) moving beyond existing standards for biodiversity conservation; (ii) embracing MSJ as a process and practice; and (iii) building the capacity of NBS planners to work with MSJ.